Systematic Review of the Prevalence of Long COVID - Woodrow, Mirembe; Carey, Charles; Ziauddeen, Nida; Thomas, Rebecca; Akrami, Athena; Lutje, Vittoria; Greenwood, Darren C; Alwan, Nisreen A (Open forum infectious diseases, 2023)
Abstract Background Long COVID occurs in those infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) whose symptoms persist or develop beyond the acute phase. We conducted a systematic review to determine the prevalence of persistent symptoms, functional disability, or pathological changes in adults or children at least 12 weeks postinfection. Methods We searched key registers and databases from January 1, 2020 to November 2, 2021, limited to publications in English and studies with at least 100 participants. Studies in which all participants were critically ill were excluded. Long COVID was extracted as prevalence of at least 1 symptom or pathology, or prevalence of the most common symptom or pathology, at 12 weeks or later. Heterogeneity was quantified in absolute terms and as a proportion of total variation and explored across predefined subgroups (PROSPERO ID CRD42020218351). Results One hundred twenty studies in 130 publications were included. Length of follow-up varied between 12 weeks and 12 months. Few studies had low risk of bias. All complete and subgroup analyses except 1 had I2 ≥90%, with prevalence of persistent symptoms range of 0%–93% (pooled estimate [PE], 42.1%; 95% prediction interval [PI], 6.8% to 87.9%). Studies using routine healthcare records tended to report lower prevalence (PE, 13.6%; PI, 1.2% to 68%) of persistent symptoms/pathology than self-report (PE, 43.9%; PI, 8.2% to 87.2%). However, studies systematically investigating pathology in all participants at follow up tended to report the highest estimates of all 3 (PE, 51.7%; PI, 12.3% to 89.1%). Studies of hospitalized cases had generally higher estimates than community-based studies. Conclusions The way in which Long COVID is defined and measured affects prevalence estimation. Given the widespread nature of SARS-CoV-2 infection globally, the burden of chronic illness is likely to be substantial even using the most conservative estimates. In a review of 130 publications, prevalence estimates of Long COVID (>12 weeks) after SARS-CoV-2 infection differed according to how persistent symptoms were identified and measured, and ranged between 0% and 93% (pooled estimate, 42.1%; 95% prediction interval, 6.8%–87.9%).